2004
DOI: 10.1002/elan.200302910
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Electrochemical Oxidation Pathway of Ammonia in Dimethylformamide and the Room Temperature Ionic Liquid, 1‐Ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide

Abstract: The direct electrochemical oxidation of ammonia has been examined in both the organic solvent dimethylformamide (DMF) and the room temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [EMIM][N(Tf) 2 ]. The corresponding voltammetric responses have been shown to be similar in each solvent with a broad oxidative wave occurring upon the introduction of ammonia to the solution and the appearance of a new reductive wave following the oxidation. The oxidative reaction process has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 26 publications
7
58
0
Order By: Relevance
“…is observed, and is attributed to the direct oxidation of ammonia at the electrode surface, consistent with the previous observation by Buzzeo et al [5] in the RTIL [C 2 mim] [NTf 2 ]. The peak potential of this wave becomes more negative when the scan rate is increased, indicating electrochemical irreversibility, as confirmed by Tafel analysis of the linear region between 10% and 90% of oxidation peak current.…”
Section: Cyclic Voltammetry Of Ammonia In [C 4 Mim] [Bf 4 ]supporting
confidence: 92%
See 3 more Smart Citations
“…is observed, and is attributed to the direct oxidation of ammonia at the electrode surface, consistent with the previous observation by Buzzeo et al [5] in the RTIL [C 2 mim] [NTf 2 ]. The peak potential of this wave becomes more negative when the scan rate is increased, indicating electrochemical irreversibility, as confirmed by Tafel analysis of the linear region between 10% and 90% of oxidation peak current.…”
Section: Cyclic Voltammetry Of Ammonia In [C 4 Mim] [Bf 4 ]supporting
confidence: 92%
“…From the voltammetry presented in Figure 3, it is suggested [5] that the electrochemical oxidation of ammonia likely proceeds via the following electrochemical step, which occurs at ca. þ 1.6 V at the GC electrode:…”
Section: Voltammetry Of Ammonia In Propylene Carbonatementioning
confidence: 98%
See 2 more Smart Citations
“…Various studies have focussed on the electrochemical oxidation of ammonia in alkaline solutions, 39 and as a result, several protocols based on its determination via its direct oxidation have been developed. Mechanistic studies for the oxidation of ammonia have been reported in the aprotic solvents acetonitrile (MeCN), 40 dimethyl formamide (DMF), 41 propylene carbonate (PC), 42 Figure 8 shows the oxidation of ammonia (10% NH 3 , 90% N 2 ) on a Pt microdisk electrode (diameter = 10 m) in the RTIL [C 4 mim][BF 4 ] at a scan rate of 10 V s -1 . Peak I corresponds to the direct oxidation of ammonia, and peaks II, III and IV have been shown 18 to be due to the following electro-generated products; the solvated proton (H[BF 4 ] x ), ammonium ion (NH 4 + ) and adsorbed hydrogen (H 2 ) respectively.…”
Section: Oxidation Of Ammoniamentioning
confidence: 99%